Irrevogabilidade, a qualquer tempo, dos benefícios fiscais na condição de isenções onerosas - Medeiros, Frederico Batista dos Santos (2018)
The purpose of this article is to discuss, specifically, the irrevocability of tax benefits when included in a peculiar modality of Tax Exemption, which is denominated by the doctrine of "Exemption onerous". Thus, in the present work we will discuss the peculiarities of tax benefits, conceptualizing them according to constitutional and infraconstitutional norms, and then verify the possibility of their inclusion as "tax exemption", specifically in the "onerous" modality, in order to demonstrate irrevocability of their effects at any time by the political entities that grant them, subject to the basic principles of the Federal Constitution as well as in the infraconstitutional legislation, which govern the matter.